AB0919 WHAT IS LOWER EXTREMITY ENTHESEAL INVOLVEMENT IN ACUTE GOUT ATTACK? AN ULTRASOUND-STUDY. (2nd June 2020) - Cao, H.; Xu, G.; Lin, J.
Abstract : Background: Articular involvement in acute gout attack is extremely common and mainly characterized by arthritis, which are usually transient, severe, reversible and well responsive to treatment. The involvement of tendons and entheses in lower extremity in monosodium urate-related disease through US (ultrasound) assessment have been described 1, 2 . US findings in gout raising the hypothesis that entheseal involvement could be a missing target in the clinical evaluation of gout patients. Objectives: To evaluate by ultrasound (US) the frequency and characteristics of lower extremity entheseal involvement in acute gout attack patients. Methods: US assessment were performed by independent rheumatologist on 31 patients with acute gout attack. Presence of lower extremity entheseal involvement were evaluated by grey-scale (GS) and power Doppler (PD). US assessment contain quadriceps, patellar and Achilles tendons, and plantar fascia entheses according to the OMERACT definitions. Results: US revealed one or more abnormalities in at least one enthesis in 22 out of 31 gout patients (71.0%) and 47 out of 310 entheses (15.2%). Among the affected entheses, the patellar insertion of quadriceps tendon was most commonly involved (57.4%) during acute gout attack, followed by the calcaneal insertion of the Achilles tendon (17.0%) and distal insertion of the patellar tendon (14.9%). The proximal insertion of the patellar tendon and calcaneal insertion of the plantar fascia were involved in 8.5% and 2.1%, respectively. Bone erosions and osteophytes were found in affected entheses (10.6% and 25.5%, respectively). Conclusion: Our study identifies that lower extremity entheseal involvement is a missing target in the evaluation of patients with acute gout attack. US plays a key role in the assessment of both clinical and subclinical enthesitis in gout patients. References: [1]Pineda C, Amezcua-Guerra LM, Solano C, et al. Joint and Tendon Subclinical Involvement Suggestive of Gouty Arthritis in Asymptomatic Hyperuricemia: an Ultrasound Controlled Study. J Rheumatol. 2011;38(6):1195-1195. [2]Carroll M, Dalbeth N, Allen B, et al. Ultrasound Characteristics of the Achilles Tendon in Tophaceous Gout: A Comparison with Age- and Sex-matched Controls. J Rheumatol. 2017;44(10):1487-1492. Disclosure of Interests: None declared